A future with less HLA: potential clinical applications of HLA‐universal cells. Issue 6 (10th April 2015) - Figueiredo, C.; Blasczyk, R.
Abstract The high variability of the human leukocyte antigen (HLA) remains a major obstacle to the application of allogeneic products in cell‐based therapies. We have developed a strategy to decrease the immunogenicity of cell and tissues to improve their survival after allogeneic transplantation in the absence of immunosupression. Using RNA interference technology, the expression of HLA class I and II was stably downregulated. HLA‐silenced cells demonstrated to prevent a de novo and escape a pre‐formed alloimmune response in vitro and in vivo. Also, they demonstrated to be capable of engraft and survive after allogeneic transplantation independently of the donor's and recipient's genetic background. The generation of HLA‐universal cells has may open new horizons in the field of regenerative medicine. Some of the potential clinical applications of HLA universal cells will be discussed in this review.